Maternal and Parent-of-Origin Effects on the Etiology of Orofacial Clefting - Rasevic, Nikola (Université d'Ottawa / University of Ottawa, 2021)
Objective: To investigate the association of previously reported single nucleotide polymorphisms (SNPs) in relation to orofacial clefts and assess their interaction with environmental factors. Methods: Genome-wide SNP genotypes were obtained for case-parent triads from the EUROCRAN and ITALCLEFT studies. Candidate SNPs were selected from a previous genome-wide association study (Shi et al., 2012) along with surrounding SNPS for a total of 2142 genotyped and imputed SNPs. A total of 411 case-parent triads and 25 case-parent dyads were analyzed using log-linear models to test for maternal and parent-of-origin effects along with their interaction with maternal smoking and maternal folic acid consumption. Results: A significant association (q = 0.025) was detected for a region in the ATXN3 gene. This significance refers to the interaction between maternal periconceptional smoking and maternal genetic effects. Nominally significant associations in genes relating to the brain were also detected. Conclusion: SNPs in the ATXN3 region warrant further investigation.
Keywords: Orofacial clefts; Maternal genetic effects; Parent-of-origin genetic effects; Gene-environment interaction; Case-parent trios